Nationalism, religion and community: A. B. Salem, the politics of identity and the disappearance of Cochin Jewry - James Chiriyankandath (Journal of Global History (2008) 3, pp. 21-42, 2008)
This article considers how the existence of an ancient community, the Jews of Cochin on India's Malabar coast, was transformed by the force of two powerful twentieth-century nationalisms - Indian nationalism and Zionism. It does so through telling the story of a remarkable individual, A. B. Salem, a lawyer, politician, Jewish religious reformer, and Indian nationalist, who was instrumental in promoting the Zionist cause and facilitating the mass migration of the Cochin Jews to Israel. Salem's story illustrates how the prioritization and translation of kinds of identity into the public sphere is fluid and contingent upon a variety of circumstances, personal as well as the outcome of changes in the wider world.